The Effect of Bureaucratic Simplification on Civil Servants’ Performance: The Mediating Roles of Motivation and Job Satisfaction - Happy Wulandari; Agus Joko Purwanto; Rina Herlina Haryanti (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the effect of bureaucratic simplification on the performance of civil servants in the Salatiga City Government, with work motivation and job satisfaction as mediating variables. The study employs a quantitative explanatory approach with a cross-sectional survey design. Data were collected from 148 civil servants selected through proportional random sampling from a population of 2,883 employees, supported by interviews with five public service users. The variables were measured using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The results show that bureaucratic simplification has a positive and significant effect on employee performance, work motivation, and job satisfaction. Job satisfaction also has a positive and significant effect on employee performance, whereas work motivation has a positive but insignificant effect on performance. In the indirect model, job satisfaction significantly mediates the relationship between bureaucratic simplification and employee performance, while work motivation does not. The findings indicate that bureaucratic simplification improves employee performance not only through direct structural efficiency but also through the enhancement of employees’ job satisfaction. This suggests that the effectiveness of bureaucratic reform depends not only on streamlining procedures and structures but also on the extent to which the reform creates a more satisfying work environment for civil servants.